OD-VR-Cap: Image captioning based on detecting and predicting relationships between objects - Nguyen Van Thinh; Lang, Tran Van; Van, Van The Thanh (Journal of Computer Science and Cybernetics, 2024)
Recent image captioning works often focus on global features or individual object regions within the image without exploiting the relational information between them, resulting in limited accuracy. In this paper, the proposed image captioning model leverages the relationships between objects in the image to fully understand the content and improve accuracy. The approach goes through the following steps: First, objects in the image are detected using an object detection model combined with a graph convolutional network (GCN). From this, a relationship prediction model based on relational context information and knowledge is proposed to classify relationships between objects to create a relationship graph to represent the image. Subsequently, a dual attention mechanism is built to enable the model to focus on relevant parts of both object regions and vertices in the relationship graph when generating captions. Finally, an LSTM network with dual attention is trained to generate captions relying on the image representation and given captions. Experiments conducted on MS COCO and Visual Genome datasets demonstrate that the proposed model achieves higher accuracy compared to baseline methods and some recently published works.